Editorial - Machado Jr., Cláudio de Sá; Souza, Ângelo Ricardo de (Educar em Revista, 2017)
Educar em Revista v. 33, n. especial 3 (2017) Dossiê - Inclusão e acessibilidade: desafios da Educação Superior